Penegakan Hukum Terhadap Pertambangan Emas Tanpa Izin oleh Kepolisian Sektor Kecamatan Singingi - Hana Aulia Putri (Lex Renaissance, 2020)
Unlicensde gold mining still occurs very often in Singingi District, leading to negative impacts on the environment. This research was conducted to determine the law enforcement against unlicensed gold mining (PETI) by the Singingi District Police and the obstacles. This is an empirical juridical or sociological legal research carried out by identifying the law and how the effectiveness of the law applies. The results conclude that the efforts made in the context of law enforcement of the PETI crime are preventive and repressive efforts. However, these law enforcement efforts have obstacles that cause ineffective PETI law enforcement by the Singingi District Police, namely the lack of supporting facilities and infrastructure, lack of coordination, both between the government and the community, and the lack of enforcement of existing indigenous law